Mining CFD Algorithm on Medium Dataset Using Queue - Baghel, Purva; Pohekar, Poorva; Gahukar, Suhani; Pinjarkar, Latika; Agrawal, Poorva; Kaur, Gagandeep (2024 IEEE 6th International Conference on Cybernetics, Cognition and Machine Learning Applications (ICCCMLA), 2024)
Database and Data Mining is an important domain in the IT Sector as maintenance of big data leads to an increase in the accuracy and efficiency of projects working on the basis of the same datasets. In this research paper, the main aspect of data mining is discussed i.e., effective algorithms used for data mining and data analysis. We have discussed the algorithm for data mining CFD (Conditional Functional Dependency). Our goal is to find high-quality CFD relation sets. We have applied CFD on our college's medium data to filter the dirty items. In this experiment, we used a standard CFD and data structure like a queue to clean our data. We have selected the data of our college to clean up the data of the students who have left or didn't pass the degree. We evaluate our set of CFD by comparing them with the number of students enrolled and the number of degrees allotted to the students. We have also given examples on a small-scale basis about the above techniques and methods.